Are palm reversals the pronoun reversals of sign language? Evidence from a fingerspelling task - Shield, Aaron; Igel, Megan; Meier, Richard P. (Frontiers in Psychology, 2022)
Acquisition of pronominal forms by children with autism spectrum disorder (ASD) continues to garner significant attention due to the unusual ways that such children produce and comprehend them. In particular, pronoun reversal errors (e.g., using the 2nd-person pronoun ‘you’ to refer to oneself) have been noted in the speech of children with ASD since the very first report of the disorder. In more recent years, investigations of the signing of deaf children with ASD have documented a different phenomenon: palm orientation reversals, such that signs typically produced with an outward-facing palm are produced with the palm towards the signer, or vice versa. At the same time, true pronoun reversals have yet to be documented in the signing of deaf children on the autism spectrum. These two curious facts have led us to ask if there is evidence that palm orientation reversals in signed languages and pronoun reversals in spoken languages could be surface manifestations of the same underlying differences present in ASD. In this paper we seek to establish whether there is evidence for such an analogy, by comparing the ages at which the two phenomena appear in both typically-developing (TD) children and those with ASD, the frequency and consistency with which they appear, and their relationships with other linguistic and cognitive skills. Data are presented from a fingerspelling task given to a sample of 17 native-signing children with ASD and 24 native-signing TD children. We conclude that there are provocative parallels between pronoun reversals in spoken languages and palm reversals in signed languages, though more research is needed to definitively answer these questions.